Aceh Traditional Culinary Kuah Pliek U: How it Sustains Eco-Lexicon Diversity - Zurriyati, Zurriyati; Yuliza, Yuliza; Zulfikar, Teuku; Perangin-angin, Alemina Br. (Jurnal Ilmiah Peuradeun, 2023)
"Kuah Pliek" is the famous Acehnese cuisine that utilizes most ecological materials. However, only a few researchers have discussed the sustainability of the lexicon contained within the cuisine from an eco-linguistics perspective. This study focuses on Aceh's traditional cuisine, "Kuah Pliek U" (KPU), to assess the raw materials' eco-lexicon diversity and the Acehnese's knowledge of the identified eco-lexicon. This study employed a qualitative research design to address the problems in which data collection included in-depth interviews, Focus Group Discussions (FGDs), passive and active observation, and the examination of documents such as research reports and journal articles. The analysis of data then used a qualitative interactive model. The result demonstrates that the number of the eco-lexicon within KPU is about 35 – 40, as same as its total of raw materials and ingredients. It consists of biotic and abiotic, with plants comprising the majority. Linguistically, the lexicon belongs to the noun class, but semantically, it can be divided into nouns, prepositional eco-lexicons, and nouns and conjunction. This study also reveals that Acehnese knowledge of KPU has decreased, despite its continued popularity in Aceh society. It means that the existence of three dimensions that influence language sustainability cannot guarantee that local people's cultural knowledge will remain intact.